Disney princess enchanted character guide - Saunders, Catherine; Hester, Beth Landis (New York DK Publishing, 2014)
"Journey into the enchanting worlds of the Disney princesses, where dreams really do come true. Discover wonderful tales of adventure, romance, and magic, meeting all your favorite characters along the way."--P. [4] of cover
Snow White and the seven dwarfs -- Cinderella -- Sleeping Beauty -- The Little Mermaid -- Beauty and the Beast -- Aladdin -- Pocahontas -- Mulan -- The Princess and the Frog -- Tangled -- Brave
1
Keywords: Disney characters -- Juvenile literature; Princesses -- Juvenile literature